Monoclonal antibodies in rheumatoid arthritis. (October 2013) - Cohen, Marc; Omair, Mohammed A; Keystone, Edward C
Monoclonal antibodies are a group of complex and effective biologic agents used in the treatment of rheumatoid arthritis and other immune-mediated inflammatory diseases. They now represent an important series of options in the treatment of rheumatoid arthritis. In this review, we discuss the efficacy and safety of these agents. In addition, information regarding upcoming monoclonal agents and biosimilars is presented.